Program Pemberdayaan Lansia: Meningkatkan Kesehatan, Pengetahuan, Dan Kemandirian Dalam Masyarakat - Sa`adah, Haqiqotus; Marianingsih, Ita; Sa’datut Daroini (Bengkulu Institute, 2025)
Empowerment of the elderly plays a crucial role in enhancing their quality of life, particularly in aspects of health and independence. The elderly often face various challenges, such as physical decline, chronic diseases, and social limitations that impact their quality of life. Therefore, empowerment through health education and skills training is essential to improve the elderly's ability to manage their health independently. This study aims to explore the effectiveness of an elderly empowerment program focused on increasing health knowledge, disease management skills, and strengthening independence in daily activities. The program is implemented with a participatory approach, involving the elderly actively in every stage of the activity, from training to evaluation. Through health counseling, physical training, and social support, it is hoped that the elderly will be able to address their health issues and improve social interactions within their communities. The expected outcomes include increased knowledge about healthy lifestyles, the ability to manage personal health, and enhanced independence in daily life. This program is also expected to serve as an empowerment model that can be applied in various regions to sustainably improve the well-being of the elderly.